INTERVENSI ASPEK KESEHATAN LINGKUNGAN DALAM MENCEGAH KEJADIAN STUNTING - Junaidi; Pratiwi, Niken; Parellangi; Pahruddin, Muhammad; Ali, Zulfikar; Hamzani, Sulaiman; Haris, Abdul; Suroto; Afifah Puteri, Siti Noor Ain; Farhat, Yasir; Ahdiyannor, Muhammad Isra (JURNAL RAKAT SEHAT (JRS) : Pengabdian Kepada Masyarakat, 2025)
Melayu Tengah Village is one of the villages located in East Martapura District, Banjar Regency, South Kalimantan Province. With strategic village potential, it has a connecting bridge with East Martapura District and other villages, the existence of Pukaha craftsmen, and community support for health. However, health problems still occur frequently, such as diarrhea and stunting. Banjar Regent H. Saidi Mansyur said that based on the results of the 2021 Indonesian toddler nutrition case study, the prevalence of stunting in Banjar Regency was 40.2%. (Banjar Regency Public Info, (20 May 2022). Even though the threshold set by the World Health Organization or WHO for stunting cases is only around 20 percent. Moreover, prevalence rates above around 30 percent are declared as 'red' status areas.   After the previous year the team carried out increased sanitation efforts, one of which was through increasing community knowledge in the target area of ​​ Melayu TengahVillage, East Martapura District, Banjar Regency, community service in 2024 will focus on interventions on environmental health aspects in the form of building faecal disposal facilities and household wastewater management. It is hoped that the stairs will become an example and even become a habit for the community in their daily lives, so that they can prevent the transmission of infectious diseases which have a further impact on the incidence of stunting.